Qadar in classical and modern Islamic discourses:commending a futuristic perspective - Wan Fariza Alyati Wan Zakaria, (Universiti Kebangsaan Malaysia, 2015)
In classical Islamic era, the discussion on the concept of fate (divine predestination) or qadar has created various debates with regard to its relationship to the problem of freedom (hurriya), choice (ikhtiyar) and free will (irada). The word qadar has been treated differently by various Islamic thinkers such as the jurists, the Sufis, the philosophers and the theologians (mutakkalimun) according to their respective concern. Classical discourse on qadar is found predominantly in debates between two main sects, the Murji’ites and the Jabarites who believe that God had predetermined the human life at one hand, and the others, the Muktazilites and the Qadarites who believe in human’s free will. The modern discourse on qadar shifts to different tunes. It is believed that qadar was responsible for paralyzing the energies of the Muslims and was the chief cause of their moral degeneration. The doctrine of qadar causes the Muslims to regard all their actions and achievements as dependent on the will of God and, for the same reason, they were unable to safeguard their rights and protect their countries from tyranny – thus obstructing their overall progress. This paper attempts at discussing both the classical and modern Islamic conceptions of qadar and its dynamism as the source of strength for Muslims to think about the future in positive attitude - that it is the only space which they could actively participate and operate in order to choose their destiny, be it good or bad, whether on the earth as God’s servants and vicegerents, as well as in the hereafter where they will taste the consequences of their actions. Understanding the true concept of qadar and also its dynamic association with the organic concept of time is about knowing the consequences of human actions and this is the very basic of futures thinking in Muslim mind.